SAAT-SAAT KRITIS BAHASA CIA-CIA - Iqbal Nurul Azhar (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2011)
Cia-Cia language is one of endangered local languages. Its status as a local language along with the bad condition of its speakers put this language in a highly risk of extinction. The latest policy issued by Bau-Bau’s government to teach Hangeul writing system to Cia-cia people have worsen Cia-Cia’s condition. Not only the policy is so controversial, but also can speed up the extinction process of Cia-cia language. This papers aims to expose how danger it is to let the Bau-Bau’s government continue the policy. Once the policy launched, we may count the Cia-Cia’s extinction time backward.